2020
DOI: 10.1007/s00256-020-03394-z
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of abnormal findings in 230 knees of asymptomatic adults using 3.0 T MRI

Abstract: Objective To identify abnormalities in asymptomatic sedentary individuals using 3.0 Tesla high-resolution MRI. Materials and methods The cohort comprised of 230 knees of 115 uninjured sedentary adults (51 males, 64 females; median age: 44 years). All participants had bilateral knee 3.0 T MRIs. Two senior musculoskeletal radiologists graded all intraarticular knee structures using validated scoring systems. Participants completed Knee Injury and Osteoarthritis Outcome Score questionnaires at the time of the MRI… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
31
2
6

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 56 publications
(40 citation statements)
references
References 56 publications
1
31
2
6
Order By: Relevance
“…The rate of SONK was much lower in this study compared to previous literature (0.3% vs 3.4%) [17]. A reason for this is the range of patients included in this study was 1-98 and SONK has been found to be more common in older patients [17]. As a result, the overall rate is expected to be lower in this study as we included patients of all ages, whereas the previous study only included patients above 50 years old.…”
Section: Discussioncontrasting
confidence: 89%
See 1 more Smart Citation
“…The rate of SONK was much lower in this study compared to previous literature (0.3% vs 3.4%) [17]. A reason for this is the range of patients included in this study was 1-98 and SONK has been found to be more common in older patients [17]. As a result, the overall rate is expected to be lower in this study as we included patients of all ages, whereas the previous study only included patients above 50 years old.…”
Section: Discussioncontrasting
confidence: 89%
“…The rate of ACL ligament rupture found in this study was lower than previously reported (8% vs 17%) [14]. The rate of SONK was much lower in this study compared to previous literature (0.3% vs 3.4%) [17]. A reason for this is the range of patients included in this study was 1-98 and SONK has been found to be more common in older patients [17].…”
Section: Discussioncontrasting
confidence: 66%
“…One explanation for the modest effect sizes may be the clinical complexity and heterogeneity of people with OA associated knee pain (Sinikallio et al., 2014). While radiological evidence of degeneration is a sentinel feature of knee OA, such findings are highly prevalent in pain free individuals (Horga et al., 2020) and the degree of structural change is not strongly associated with levels of reported pain (Bedson & Croft, 2008), suggesting that other factors require consideration. For example, people with higher Body Mass Index (BMI) experience greater pain than individuals with lower BMI even when taking into account OA severity (Weiss, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…2). Supplemental searches were performed to expand on key topics identified in the original literature search, i.e., subchondral bone pathology [1], knee sleeves [2][3][4][5][19][20][21], bone marrow lesions [22][23][24][25][26], clinical risk factors for knee OA progression [27][28][29][30][31][32][33], OA phenotypes [34], nonpharmacological treatments for OA [35][36][37][38][39][40][41][42][43], and clinical practice guidelines for OA management [44].…”
Section: Literature Searchmentioning
confidence: 99%
“…Bone marrow lesions (sometimes called bone marrow edema) have been demonstrated to be present in individuals without [8,22] and with [23] clinical OA; to wax and wane with weight-bearing activity (e.g., in marathon runners [24,25]); and to be associated with incident knee pain in individuals at risk of OA [26], and with pain and disability for activities of daily living in patients with established OA [9]. Joint fluid overload correlates with symptoms.…”
Section: Comparison With Other Studiesmentioning
confidence: 99%